Recruitment of Condensin to Replication Origin Regions by ParB/SpoOJ Promotes Chromosome Segregation in B. subtilis - Gruber, Stephan; Errington, Jeff (Cell, 2009)
Proper segregation of DNA replication products is essential in all cells. In Bacillus subtilis, two protein complexes have been implicated in this process: the ParAB homologs, Soj and Spo0J, and the bacterial Smc/ScpAB complex, also called condensin. Here we demonstrate that Smc is highly enriched in the region around the origin of replication, specifically near parS sites to which Spo0J binds and at highly transcribed genes. Furthermore, we find that efficient recruitment of Smc to a large region around the origin of replication depends on the presence of Spo0J. We show that Spo0J performs two independent functions: regulation of initiation of DNA replication via Soj and promotion of chromosome segregation by Smc recruitment. Our results demonstrate a direct functional interaction between two widely conserved systems involved in chromosome replication and segregation.